The American and European Revolutions, 1776-1848: Sociopolitical and Ideological Aspects, wyd. J. Pelenski - Rosner, Anna (Czasopismo Prawno-Historyczne, 1983)
Recenzja: The American and European Revolutions, 1776-1848: Sociopolitical and Ideological Aspects. Proceedings of the Second (Bicetennial) Conference of Polish and American Historians Iowa City, Iowa, USA. 29 September — 1 October 1976, wyd. Jaroslaw Pelenski, University of Iowa Press 1980, ss. 412.